Exogenous misfolded protein oligomers can cross the intestinal barrier and cause a disease phenotype in C. elegans - Michele Perni (Nature Portfolio, 2021)
Abstract Misfolded protein oligomers are increasingly recognized as highly cytotoxic agents in a wide range of human disorders associated with protein aggregation. In this study, we assessed the possible uptake and resulting toxic effects of model protein oligomers administered to C. elegans through the culture medium. We used an automated machine-vision, high-throughput screening procedure to monitor the phenotypic changes in the worms, in combination with confocal microscopy to monitor the diffusion of the oligomers, and oxidative stress assays to detect their toxic effects. Our results suggest that the oligomers can diffuse from the intestinal lumen to other tissues, resulting in a disease phenotype. We also observed that pre-incubation of the oligomers with a molecular chaperone (αB-crystallin) or a small molecule inhibitor of protein aggregation (squalamine), reduced the oligomer absorption. These results indicate that exogenous misfolded protein oligomers can be taken up by the worms from their environment and spread across tissues, giving rise to pathological effects in regions distant from their place of absorbance.